Perennial onion is a plant of nourishing and medicinal properties - A. F. Agafonov; N. S. Dudchenko; N. A. Golubkina (Овощи России, 2009)
Vegetables are a source of vitamins, salts, acids, carbohydrates and biologically active substances which are necessary for human's vital function. Academician Pavlov I.V. asserted that life expectancy of human can be one third longer by daily consumption of fresh vegetable. The nourishing values of vegetables are composed not only of high content of carbohydrate and proteins, but also there is an extremely useful source of vitamins and ferments, microelements and biologically active substances. It should be mentioned that some of necessary substances can dissociate or transform under the thermal condition in another ones, sometime, not accessible chemical forms. Taking this into account the human's food must be enriched by vegetables that bring natural consistencies of substances. The perennial onion can be used as a vegetable with all these qualities.